PENGARUH CITRA MEREK TERHADAP MINAT BELI WISATAWAN PADA KOMANEKA RESORTS & SPA GROUP DI KAWASAN PARIWISATA UBUD, GIANYAR - I Nyoman Wiratnaya (Institut Pariwisata dan Bisnis Internasional, 2014)
The growth of Ubud district as famous tourist destination in Gianyar regency implies a tight competition in hotel industry at this area to capt potential markets, especially foreign tourists. To take a strategic market advantages, hotel industry in Ubud Area supposed to relies on productâ€™s attibut function and brand image. Recently, hotel industry recognized â€œbrandâ€ as a very important asset that can attract potential customerâ€™ purchase intention.Â Customer recognized brand as not just name, sign or symbol, but brand is a promises, prestiges, social status, or values of hotel supposed to give their customers features, benefits, and services. This study aimed to explore the impact of Brand Image on touristâ€™ purchase intention at Komaneka Resorts & Spa group which consists of Komaneka at Monkey Forest, Komaneka at Tanggayuda, Komaneka at Bisma, and Komaneka at Rasa Sayang, Ubud. The methodology applied at this study is symple regression model with SPSS 17.00. This methodology was chosen because this study assumed â€œbrandâ€ influenced tourist intention to purchase.The findings of this study was thereâ€™s a significant impact of brand image on purchase intention at Komaneka Resorts & Spa Group, Ubud, Gianyar with R Squared 0,616. This means 61,6 % of touristâ€™s purchase intention influenced by brand image, and 38,4 % influenced by others factors.This study recommend hotel managers to develop and improve their hotelâ€™s brand image to grap strategic market position.